Controllability of control systems on complex simple lie groups and the topology of flag manifolds - Santos, Ariane Luzia dos [UNESP]; Martin, Luiz Antonio Barreira San (Springer Nature, 2013)
Let S be a subsemigroup with nonempty interior of a connected complex simple Lie group G. It is proved that S = G if S contains a subgroup G (α) ≈ Sl (2, C) generated by the exp g±α, where gα is the root space of the root α. The proof uses the fact, proved before, that the invariant control set of S is contractible in some flag manifold if S is proper, and exploits the fact that several orbits of G (α) are 2-spheres not null homotopic. The result is applied to revisit a controllability theorem and get some improvements.
Keywords: Controllability; Simple Lie groups; Flag manifolds